Radon concentration variations at the Yangyang underground laboratory - Ha, C.; Jeong, Y.; Kang, W. G.; Kim, J.; Kim, K. W.; Kim, S. K.; Kim, Y. D.; Lee, H. S.; Lee, M. H.; Lee, M. J.; Lee, Y. J.; Seo, K. M. (Frontiers in Physics, 2022)
The concentration of 222Rn in the air has been measured in the 700 m-deep Yangyang underground laboratory between October 2004 and May 2022. The average concentrations (spreads) in two experimental areas, called A6 and A5, were measured to be 53.4 Bq/m3 (13.9 Bq/m3) and 33.5 Bq/m3 (7.9 Bq/m3), respectively. The lower value in the A5 area reflects the presence of better ventilation. The radon concentrations sampled within the two A5 experimental rooms’ air are found to be correlated to the local tunnel temperature outside of the rooms, with correlation coefficients r = 0.22 and r = 0.70. Therefore, the radon concentrations display a seasonal variation, because the local temperature driven by the overground season influences air ventilation in the experimental areas. A sinusoidal function with a period of one year was used to fit the radon concentration data of both underground areas finding a maximum amplitude on August, 31 ± 6 days.